BUDDHISM THOUGHT IN DAILY JAPANESE VOCABULARY - Pamugari, Alpina; Sunarti, Herlina; Sari, Rima Novita; Tanjungsari, Yosefa P. (Ikatan Dosen Menulis, 2025)
Buddhism has had a profound and lasting impact on Japanese daily life, influencing everything from social structures and personal values to rituals and aesthetics. The spread of Buddhism to Japan, beginning around the 6th century, introduced various philosophies, practices, and customs that continue to shape Japanese culture today. One of the most popular Buddhist sects among the Japanese is Nichiren, which has been quite active in spreading its teachings, even internationally. According to the official Nichiren website, 185 daily Japanese vocabulary terms are found to have been unconsciously shaped by Buddhist thought. Foreign learners of Japanese, particularly those who are not adherents of Buddhism, may face challenges in accurately translating these terms into their native languages. Based on this, vocabulary derived from Buddhist thought is analyzed.